Active methodologies as interdisciplinary praxis in vocational and technological education (Research, Society and Development, 2021)
This study is based on the struggle to overcome fragmented knowledge and proposes to reflect on the need for methodologies that encourage students to interact effectively in the world in which they live in view of the construction of knowledge integrated to the most diverse social practices. Its main objective is to produce theoretical-methodological subsidies, through a workshop, with a view to enhancing interdisciplinary practices, built from active methodologies, which provide the interrelationship between introductory and technical disciplines in the context of Professional and Technological Education. The research was based on a qualitative approach from an Action Research perspective and was developed based on the historical-critical pedagogy. Data and information were collected and generated through a Likert scale, bibliographic collection, conversation wheel and questionnaire. On that occasion, a workshop entitled “Ecological Awareness” was applied using Active Methodologies. The proposal was worked on with EMI students in Agroecology and Environment and proved to be a possibility of a viable strategy in the struggle for the formation of emancipated subjects who see in the opportunity of interdisciplinary know-how, possibilities for significant learning, in line with complexities of the contemporary world.